Functional and Radiological Outcome of Surgical Management in Lumbar Spinal Stenosis – A Comparative Study - Makesh Ram Sriraghavan; Kandasamy Natesan; Pavalan Louis; Harish Shanmugam Punniakotti; Naveen Venkidusamy; Namala Sai Vinay Bharadwaj (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Lumbar spinal stenosis (LSS) is a clinical syndrome with neurogenic claudication, low back ache, with radiating pain to lower limbs, due to a decrease in spinal canal dimensions. Degeneration is the most common etiology, resulting due to facet joint arthropathy and intervertebral disc protrusion. Surgical intervention should be considered when conservative methods fail or if there is a progressive worsening of signs or symptoms. Most of surgical techniques are based on the principles of decompression with or without stabilization and fusion. Two or more levels of laminectomy with stabilization and fusion provide effective spinal stability but have limited adverse effect. Methodology: This is a study of 40 patients with lumbar canal stenosis, who were admitted in Thoothukudi Medical College Hospital, from July 01, 2016, to August 01, 2022. The patients admitted were allocated alternatively into two groups, decompression alone and decompression with stabilization/fusion with 20 cases each, respectively. Results: Both the groups were analyzed preoperatively and postoperatively based on demographic criteria and on clinical history, radiographic angle measurements, and Oswestry Disability Index. Conclusion: The diagnosis of LSS is often challenging and requires proper clinical assessment of the patients and their symptoms and correlates with the radiological findings. Considering these, we suggest decompression alone may be considered rather than stabilization and fusion in patients with less than two-level stenosis and stabilization with fusion more than two levels.